Design and fabrication of reliability test fixtures (hook button stroke) - Muhammad Izzat, Haslan (2009)
The objective of the report is about the solution of the problem that Panasonic Comunication Malaysia in Johor Bahru faced on running the test for the Hook Button Stroke for Integrated Telephone System (ITS) model. As usual, this telephone usually was put in any position like on the desk, hanging on the wall, and others. For that case, this test must be done to improve the quality for this telephone model. Nowadays, the company just run their test by hand and ruler, no specific device for it. For that reasons, this project were done to make sure and to solve this problem. With this device, hopefully it can help in make it sure the test can be running with more efficient and effective besides can improve the quality of the product to be market either in local and international market fields.